Experimental investigation and optimization of the gasification parameters of macadamia nutshells in a batch-fed bubbling fluidized bed gasifier with air preheating - Fredrick Irungu Njuguna; Hiram M. Ndiritu; Benson B. Gathitu; Meshack Hawi; Jotham Muthoka Munyalo (Energy Storage and Saving, 2023)
Gasification of biomass waste has a significant potential to reduce environmental impact and promote sustainability by producing syngas, which is considered as renewable energy. This work investigated the gasification of macadamia nutshells in air-preheated, batch-fed fluidized bed gasifier. The study conducted a parametric analysis to assess the effect of equivalence ratio (ER) and air temperature on the gasifier temperature profile and its performance based on gas composition, higher heating value (HHV), and gas yield. The research was conducted within the range of 0.15–0.35 for the ER and 25–825 °C for the air temperature. Multi-objective numerical optimization was conducted using response surface methodology (RSM). From the parametric study, a distinct temperature profile was observed along the gasifier height, with the peak temperature near the top of the fluidized bed section and the lowest temperature at the top of the gasifier. Air preheating mostly favored gasification temperature at the lower part of the gasifier and showed rare significance at the top. No improvement in gasifier performance was observed beyond an air temperature of 620 °C, which was identified as the ideal air-preheating temperature. Analysis of variance (ANOVA) revealed that the ER was the most influential parameter in the production of combustible gasses, syngas HHV and gas yield. Air preheating did not have a significant effect on methane production and gas yield. The most optimal values for ER and air temperature were obtained as 0.195 °C and 620 °C, respectively, producing optimal values of 9.54, 14.65%, 2.03, 4.02 MJ·Nm−3, and 1.82 Nm3·kg−1 for hydrogen, carbon monoxide, methane, HHV, and gas yield, respectively.